2023
DOI: 10.5194/egusphere-egu23-5788
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stratospheric aerosol size decrease after volcanic eruptions

Abstract: <p>The evolution of the size distribution of stratospheric aerosols after volcanic eruptions is still not understood very well, due to the temporal sparsity of in situ measurements, the low spatial coverage by ground based observations and the difficulties to derive aerosol size information from satellite measurements. To contribute to this ongoing research, we show data from our aerosol size retrieval using SAGE III/ISS solar occultation measurements. Using a three wavelength extinction approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The homogeneity and the persistence of the properties across the plume and in time are clearly visible. Using the same method, Wrana et al (2023) found σ values for other stratospheric volcanic plumes produced by the eruptions of Ambae in 2018, Raikoke and Ulawun in 2019 and La Soufrière in 2021, which are all larger, approaching respectively 1.5-1.6 and 1.8-2.0 (Wrana et al, 2023), reinforcing the exceptional aspect of the HTHH eruption.…”
Section: Resultsmentioning
confidence: 78%
“…The homogeneity and the persistence of the properties across the plume and in time are clearly visible. Using the same method, Wrana et al (2023) found σ values for other stratospheric volcanic plumes produced by the eruptions of Ambae in 2018, Raikoke and Ulawun in 2019 and La Soufrière in 2021, which are all larger, approaching respectively 1.5-1.6 and 1.8-2.0 (Wrana et al, 2023), reinforcing the exceptional aspect of the HTHH eruption.…”
Section: Resultsmentioning
confidence: 78%
“…Using the same method, Wrana et al. (2023) found σ values for other stratospheric volcanic plumes produced by the eruptions of Ambae in 2018, Raikoke and Ulawun in 2019, and La Soufrière in 2021, which are all larger, approaching 1.8–2.0 together with smaller sizes (Wrana et al., 2023), reinforcing the exceptional aspect of the HTHH eruption.…”
Section: Resultsmentioning
confidence: 94%
“…For comparison, Wrana et al. (2023) found density of 20–30 cm −3 in stratospheric volcanic plumes generated by other recent eruptions with similar sulfur injection but much smaller particles.…”
Section: Resultsmentioning
confidence: 97%
“…This finding is supported by routine balloon-borne measurements conducted over Boulder, Colorado (40° N, 105° W), which show a consistent trend upon comparing data from the summers of 2021 and 2020, as well as the spring of 2019 before the Raikoke eruption (see Figure S8 in the Supplement). The reduction in stratospheric aerosol size following the 2021 La Soufrière eruption is also indicated by SAGE III/ISS satellite retrievals (Wrana et al, 2023).…”
Section: Aerosol Concentration and Size Distribution From Aircraft Me...mentioning
confidence: 73%